P102 Integration of clinic services with online sexually transmitted infection (STI) testing (sh:24) in camberwell, se london: impact of active referral of asymptomatic testing online in 2016. (8th June 2017) - Turner, Katy ME; Zienkiewicz, Adam; Looker, Katharine; Barnard, Sharmani; Brady, Michael; Sa, Joia da; Holdsworth, Gillian; Syred, Jonathan; Baraitser, Paula
Abstract : Introduction: An online service was implemented in an area with high burden of sexually transmitted infections and poor sexual health outcomes. The aim was to improve access and availability of sexual health, fully integrated within NHS services. This study looks at the impact of a change in management, whereby asymptomatic patients seeking STI testing in the GUM clinic were directed to the online service. Methods: We compared clinic attendance in 2016 before (quarter 2, Q2) and after (quarter 3, Q3) the change in clinical practice. Individual level clinic attendance data were collated and summarised as simple STI test performed (chlamydia, gonorrhoea, HIV, syphilis) or complex service required. We also compared service use by age, ethnicity and sexual orientation. Changes in pattern of clinic attendance between the quarters were analysed using a Chi 2 test. Results: There were significantly fewer simple STI tests (Chi-squared, p<0.001) and more visits requiring complex services (p<0.001) in Q3 versus Q2. Discussion: Following establishment of efficient online STI testing, the clinic changed its triage practice: asymptomatic patients seeking STI testing were directed to use the online service. The change appears to facilitate a higher proportion of more complex visits although the absolute number of visits has decreased.